Absorption spectrometric macronutrients review of soil health during taro crop production. Issue 5 (27th May 2020) - Nisha, Sofina; Prasad, Surendra
Abstract: The purpose of this study was absorption spectrometric assessment the soil health of the soil from the taro growing areas of Taveuni, Fiji. The soil samples were collected in four cycles during taro cultivation period. The soil samples were analyzed for macronutrients (Ca, Mg, K, P and NO3 – -N), soil organic matter (SOM) and soil pH. In general, the soil pH at all sites showed lower than the ideal pH (5.6–6.6) for taro planting throughout the cropping cycle. The results showed the significant loss in SOM from taro planting (15.41%) till harvesting (5.63%). Pronounced decrease in levels NO3 –_ N (18.29 to 13.86 mg kg −1 ), P (45.97 to 25.71 mg kg −1 ), K (77.90 to 22.96 mg kg −1 ), Ca (62.20 to 27.59 mg kg −1 ) and Mg (316.10 to 121.48 mg kg −1 ) were recorded from planting till harvesting for different sites. There was significant reduction in the soil macronutrients and SOM in all the four study sites and some sites showed below critical level and critical to medium levels of these nutrients in the soil at the end of the harvesting period of taro. The statistical analysis of the soil test data confirmed the declining trend of the soil health on the island of Taveuni, Fiji.